Visual attention is not limited to the oculomotor range - Hanning, Nina M. (Proc Natl Acad Sci U S A, 2019)
Both patients with eye movement disorders and healthy participants whose oculomotor range had been experimentally reduced have been reported to show attentional deficits at locations unreachable by their eyes. Whereas previous studies were mainly based on the evaluation of reaction times, we measured visual sensitivity before saccadic eye movements and during fixation at locations either within or beyond participants’ oculomotor range. Participants rotated their heads to prevent them from performing large rightward saccades. In this posture, an attentional cue was presented inside or outside their oculomotor range. Participants either made a saccade to the cue or maintained fixation while they discriminated the orientation of a visual noise patch. In contrast to previous reports, we found that the cue attracted visual attention regardless of whether it was presented within or beyond participants’ oculomotor range during both fixation and saccade preparation. Moreover, when participants aimed to look to a cue that they could not reach with their eyes, we observed no benefit at their actual saccade endpoint. This demonstrates that spatial attention is not coupled to the executed oculomotor program but instead can be deployed unrestrictedly also toward locations to which no saccade can be executed. Our results are compatible with the view that covert and overt attentional orienting are guided by feedback projections of visual and visuomotor neurons of the gaze control system, irrespective of oculomotor limitations.